Construction contemplation of cloud platform for domestic password service based on quantum secret communication - Dong WANG; Guochun LI; Xuehao YU; Zhiyu CHEN; Bingyu GE; Lei XIE; Jing TAN (Dianxin kexue)
With the increasingly serious environment of network space security,the importance of cryptography is becoming more and more prominent.There are many problems in the current application of cryptographic technology and the demand of secure and controllable password resource for key information structure is urgent.According to technology advantages and disadvantages of classical and quantum passwords were analyzed and the integration direction of quantum cryptography and classical password technology was proposed.At the same time,by giving full consideration to the development trend of cloud computing architecture,the password cloud service concept was proposed and the domestic password service cloud platform based on quantum secret communication was designed.It has positive guiding significance for building a new firewall of cyber security based on quantum secret communication.